Plasmablastic Lymphoma in a Previously Undiagnosed Human Immunodeficiency Virus-Positive Patient: A Case Report - Mehmet Ali Altay; Selmi Yılmaz; Ayşe Taş; Nelli Yıldırımyan (Acta Odontologica Turcica, 2023)
Plasmablastic lymphoma (PBL) is a rare and aggressive non-Hodgkin lymphoma subtype associated with human immunodeficiency virus (HIV) infection. PBL is extremely aggressive and has a poor response to treatment. Clinically PBL resembles a periodontal disease, Kaposi sarcoma, or melanoma. Delayed diagnosis adversely affects the treatment and life expectancy. A 52-year-old male presented with a firm intraoral mass causing a slight elevation noticeable extraorally. Radiologically, loss of lamina dura around the first premolar and loss of both vertical and horizontal bone height around the dental implant replacing the second premolar were present. The biopsy confirmed a diagnosis of PBL. Further evaluation revealed that the patient was positive for HIV. The chemotherapy regimen included etoposide, vincristine, hydroxydaunorubicin, cyclophosphamide, and prednisolone, followed by an autologous hematopoietic stem cell bone marrow transplant. This article attempts to describe the clinical presentation and histopathological evaluation of PBL, and emphasize the paramount role of biopsy, early clinical suspicion, and correct diagnosis.